2014
DOI: 10.3109/01612840.2014.924044
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Interventions to Reduce Stress in Adolescence

Abstract: Adolescence can be a stressful developmental phase, placing youth at risk for negative health outcomes. Evidence-based interventions are crucial to helping adolescents manage stress; yet, most of the literature on adolescent stress is observational and descriptive. We systematically reviewed the literature on stress management interventions for adolescents and found there is evidence to support the effectiveness of interventions that aim to develop cognitive skills among adolescents; however, most studies had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…There is also a need to explore more concerning how and in what situations stress influences young people to start drinking and the role of social interaction in facilitating this form of drinking. In addressing this association between alcohol use and stress relief, interventions could encourage young people to derive other mechanisms of coping with stress that are less harmful [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is also a need to explore more concerning how and in what situations stress influences young people to start drinking and the role of social interaction in facilitating this form of drinking. In addressing this association between alcohol use and stress relief, interventions could encourage young people to derive other mechanisms of coping with stress that are less harmful [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis and systematic reviews have been conducted to investigate what kind of stress management interventions (SMI) are available and can reduce stress in adolescence (e.g., Rew, Johnson, & Young, 2014;Regehr, Glancy, & Pitts, 2013;Durlak et al, 2011;Vo & Park, 2008). Overall, the results are promising; most studies show positive results when it comes to reducing self-reported or physiological measures of stress.…”
Section: Treatments For Stress Among Youthmentioning
confidence: 99%
“…Cumulative and simultaneous occurrences of stressors can constitute potential threats to the well-being and healthy development of children and adolescents (Colten, 2017; Eiland & Romeo, 2013; Grant et al, 2003). Adolescent stress has been related to not only health-risk behaviors, such as consuming alcohol, smoking and abusing other substances, and maintaining poor eating habits (Garcia, 2010; Jaaskelainen et al, 2014; Low et al, 2012; King, Molina, & Chassin, 2009; Rew, Johnson, & Young, 2014) but also depression (Charbonneau, Mezulis, & Hyde, 2009; Liu & Alloy, 2010; Moksnes, Byrne, Mazanov, & Espnes, 2010; Murray, Byrne, & Rieger, 2011), anxiety (Anyan & Hjemdal, 2016; Beiter et al, 2015), and suicidal behaviors (Hewitt, Caelian, Chen, & Flett, 2014; Mathew & Nanoo, 2013). Therefore, it is important to assess and understand adolescent stress using reliable and valid measurements to promote adolescent health.…”
Section: Introductionmentioning
confidence: 99%